Bottlenecks, cooperation, and competition in nascent ecosystems - Hannah, Douglas P.; Eisenhardt, Kathleen M. (Strategic Management Journal, 2019)
[Douglas P. Hannah and Kathleen M. Eisenhardt were recognized as a runner up for the 2019 Ralph Gomory Best Industry Studies Paper Award.]